Tumour Immunotherapy and Applications of Immunological Products: A Review of Literature - Angus Nnamdi Oli; Samson Adedeji Adejumo; Adekunle Babajide Rowaiye; Joyce Oloaigbe Ogidigo; Jarrad Hampton-Marcell; Gordon C. Ibeanu (Journal of Immunology Research)
Malignant tumors, characterized by uncontrolled cell proliferation, are a leading global health challenge, responsible for over 9.7 million deaths in 2022, with new cases expected to rise to 35 million annually by 2050. Immunotherapy is preferred to other cancer therapies, offering precise targeting of malignant cells while simultaneously strengthening the immune system’s complex responses. Advances in this novel field of science have been closely linked to a deeper knowledge of tumor biology, particularly the intricate interplay between tumor cells, the immune system, and the tumor microenvironment (TME), which are central to cancer progression and immune evasion. This review offers a comprehensive analysis of the molecular mechanisms that govern these interactions, emphasizing their critical role in the development of effective immunotherapeutic products. We critically evaluate the current immunotherapy approaches, including cancer vaccines, adoptive T cell therapies, and cytokine-based treatments, highlighting their efficacy and safety. We also explore the latest advancements in combination therapies, which synergistically integrate multiple immunotherapeutic strategies to overcome resistance and enhance therapeutic outcomes. This review offers key insights into the future of cancer immunotherapy with a focus on advancing more effective and personalized treatment strategies.